Evaluating the relationship between economic growth, inflation and employment : evidence from Turkey, Brazil and South Korea - Ün, Batıkan (My University, 2019)
Bu çalışmanın amacı enflasyon, ekonomik büyüme ve istihdam arasındaki ilişkiyi Türkiye, Brezilya ve Güney Kore örneklerini kullanarak açıklamaktır. Brezilya ve Türkiye yabancı yatırım ve yurtdışından gelen sıcak para ile büyüyen iki ülkedir. Bu ülkelerin enflasyon trendleri birbirine çok yakın olduğundan dolayı ekonomileri çok büyük benzerlikler göstermektedir. Güney Kore ise gelişmiş bir ülke olarak stabil bir görünümdedir. Lakin, Güney Kore örneği bize enflasyonun etkilerinin gelişmiş ve gelişmekte olan ülkelerde nasıl farklılaştığını göstermesi açısından önemlidir. Erken dönemde yapılan çalışmalar enflasyon-ekonomik büyüme ve enflasyon-istihdam arasındaki ilişkilerin pozitif yönlü olduğunu öne sürerken, yakın dönemde yazılan makaleler ve tezler bu ilişkilerin negatif olduğunu iddia ederek enflasyonun ekonomiye çok ciddi zararlar verdiğini belirtmiştir. Bu çalışmada enflasyon, ekonomik büyüme ve istihdam verileri En Küçük Kareler Yöntemi’nin Doğrusal Denklem’e uygulanması ile elde edilen sonuçlar ile tartışılmaktadır. Zaman Serisi analizi ile belirlenen bu bulgular bize ülkeler arasındaki farklılıklarıda gösterebilecek sonuçlar vermiştir. Bu çalışma 1991 ve 2016 yılları arasında Türkiye’de, Brazilya’da ve Güney Kore’de enflasyon-ekonomik büyüme ilişkisinin negatif yönlü, enflasyon-istihdam ilişkisinin ise pozitif yönlü olduğunu saptamıştır. Lakin bu bulgular her ülke için farklı hesaplama yöntemleri kullanılarak bulunmuştur. Enflasyon-ekonomik büyüme ilişkisi bulunurken bu ilişkinin çift taraflı olmasından dolayı içsellik sorunu olduğu saptanmış, bu sorunun üstesinden gelmek için merkez bankası bağımsızlığı araç değişken olarak kullanılmıştır. Merkez bankası bağımsızlığının araç değişken olarak kullanılması Güney Kore örneği dışında diğer sonuçları anlamsız hale getirmiştir. Güney Kore örneğinde ise enflasyon-ekonomik büyüme ilişkisi pozitif olarak değişmiştir.

The aim of this study is to analyze relationship between inflation, employment and economic growth by presenting evidences from Turkey, Brazil and South Korea between 1991 and 2016. Turkey and Brazil grew with the help of international loans and foreign direct investment. They have same inflationary trends. It is accepted that their economies are highly comparable to the point where economists predict trends in Turkey by observing Brazilian economy. On the other hand, South Korea is a developed country. But, Korean case is crucial to find out that how effects of inflation differ in developed and developing countries. Earlier studies examined inflation-growth and inflation-employment relationships to be positive. But, especially after the 1970s this view has changed. Recent literature emphasized on possible negative impacts of inflation by citing that inflation-growth and inflation-employment relationships to be negative and robust. This paper used Ordinary Least Squares estimation method for linear model which has inflation as an independent variable that predicts economic growth and employment. Data used in this paper consists of annual time series data between 1991 and 2016. Time series’ nature makes it possible to look at this relationship through help of country specific effects. The initial examination and regression results revealed that there is a negative and significant relationship between inflation and economic growth while inflation and employment remains positively correlated. While analyzing the relationship, it is observed that there is an endogeneity problem in inflation and growth relationship due to reverse causality. In order to solve endogeneity issue, central bank independence added to the model as an instrumental variable for inflation. However, addition of instrumental variable caused regression results to be non-robust except for South Korean case. In South Korean data, inflation-growth relationship became positive and remained robust.
Keywords: Brazil; Brezilya; Economic development; Economic Growth; Ekonomik Büyüme; Ekonomik kalkınma; Employment; Enflasyon; Finance; Güney Kore; Güney Kore Inflation; İstihdam; Maliye; South Korea; Time Series; Turkey; Türkiye; Zaman Serisi